Enhanced electrocaloric and energy-storage properties of environment-friendly ferroelectric Ba0.9Sr0.1Ti1−xSnxO3 ceramics. (June 2022) - Zaitouni, H.; Hajji, L.; Mezzane, D.; Choukri, E.; Razumnaya, A.G.; Gagou, Y.; Hoummada, K.; Alimoussa, A.; Rožič, B.; Črešnar, D.; El Marssi, M.; Kutnjak, Z.
Abstract: The electrocaloric (EC) effect and energy storage properties of eco-friendly ferroelectric Ba0.9 Sr0.1 Ti1−x Snx O3 (BSTS-x) ceramics prepared by the conventional solid-state reaction method were studied. Significant energy efficiency exceeding 80% was found in our samples. In particular, BSTS-5 and BSTS-10 samples exhibit 92% and 88% efficiency, respectively, over a wide temperature range around room temperature (RT). Direct EC measurement and an indirect method based on the thermodynamic approach were used to characterize the EC effect, and both yielded consistent results. The largest electrocaloric responsivity of 0.73 K mm/kV was obtained for BSTS-0 at 368 K with an adiabatic temperature change ΔTEC of 0.55 K at a low applied electric field of only 7.4 kV/cm. With increasing Sn-content, the EC response of BSTS-x ceramics decreases, while their diffuseness increases over an extensive temperature range, centered at RT. A significant coefficient of performance (COP > 26) was found for our samples. The obtained results demonstrate the possibility of designing eco-friendly materials with higher EC effect and energy efficiency for potential solid-state refrigeration and energy storage devices. Graphical Abstract: ga1 Highlights: Diffused phase transition has been observed in BSTS-x ceramics with higher Sn amounts. BSTS-x eco-friendly ceramics achieved a significant energy efficiency exceeding 84% near room temperature. The high electrocaloric responsivity of 0.73 K mm/kV, exceeding most lead-based materials, was obtained for BSTS-0 at 368 K. A Large coefficient of performance (COP > 26) was found for our samples.